Does the menstrual phase matter in vascular endothelial responses to acute exercise? A narrative review of the literature - Ghniem, S.; Dawson, E. A.; Tryfonos, A. (Sports, 2025)
Women have a lower age-matched cardiovascular risk than men, largely due to estrogen`s protective role in endothelial function. While exercise improves vascular health, acute vascular responses are influenced by factors such as age, fitness level, metabolic status, and exercise modality. In premenopausal women, fluctuations in estrogen levels during the menstrual cycle may further affect vascular reactivity. Here, we review current evidence on acute exercise-induced vascular responses in women, emphasizing menstrual phase influences and key biomarkers such as flow-mediated dilation (FMD), along with others including vascular conductance and pulse wave velocity (PWV). Despite limited and heterogeneous evidence, shear-induced vascular responses, (including FMD) following acute exercise, appear to be relatively stable across menstrual cycle phase, suggesting that strict phasic control may not always be necessary. However, future high-quality studies are needed to further clarify this response. In contrast, other vascular assessments that rely more heavily on neural components—such as vascular conductance and PWV—show greater estrogen sensitivity. Nonetheless, the inconsistencies between studies again underscore the need for future research with hormonal verification. Morever, adequate sample sizes, and standardized exercise protocols will improve both consistency and help develop and promote the inclusion of women in vascular research.